Arab Spring in Linguistic Consciousness of Russian- and English-Speaking Internet Users: Network Frames as Interpreting Tool - Devyatiyarov Dmitriy (Виртуальная коммуникация и социальные сети)
The article describes the representations of the Arab Spring events in the non-professional political discourse produced by Russian- and English-speaking YouTube users. The research material involved comments to videos that featured the crises in Libya and Syria. The discursive material was analyzed using the method of network frames. Network frames are cognitive structures filled with content that depends on the specific network communication environment. The research objective was to model and interpret the network frames, their content, and structure in Russian- and English-speaking non-professional political discourses about the Arab Spring. Since network frames are essentially dynamic, the material also included comments published at different times. The author developed and applied a method for analyzing the dynamics of network frames to identify the frames involved in the description of the Arab Spring in Russian- and English-language discourse. The analysis for each frame involved its structure, content, and the main trends.